Genetic patterns of repeat and multiple parasitism by screaming cowbirds, a specialist brood parasite. (September 2020) - Ursino, Cynthia A.; Strong, Meghan J.; Reboreda, Juan C.; Riehl, Christina
Abstract : Avian brood parasites lay their eggs in the nests of other species, leaving the hosts to care for the parasitic offspring. The bookkeeping hypothesis predicts that, in order to reduce competition between parasitic nestlings, female parasites should keep a mental inventory of host nests that they have already parasitized and avoid laying multiple eggs in the same host nest. However, selection against repeat parasitism should be weaker when host nests are limited, or when hosts are able to rear more than one parasitic nestling. Here we use microsatellite genotyping of parasitic eggs to test whether female screaming cowbirds, Molothrus rufoaxillaris, avoid repeatedly parasitizing nests of their primary host, the greyish baywing, Agelaioides badius, in Argentina. Parasitism rates were extremely high (96.5% of 57 host clutches were parasitized with an average of 5.7 cowbird eggs each), indicating that host nests are limited. Although eggs laid by the same female showed moderate spatiotemporal clustering, individual females rarely laid more than one egg in the same host clutch (2 of 57 clutches, 26 of which contained multiple genotyped cowbird eggs). Females were much more likely to lay subsequent eggs in different host nests than to return to the same host nest. We found no evidence for kin structure among female cowbirds parasitizing the same host nest, which were no more closely related than chance would predict. These results suggest that female screaming cowbirds frequently lay eggs in host nests that have already been parasitized by unrelated females. However, they typically lay just one egg per host clutch, even though greyish baywings are capable of rearing several nestlings. Since screaming cowbird laying is often poorly synchronized with that of their host, avoidance of repeat parasitism may be adaptive if it allows females to spread the risk of failure among multiple host nests. Highlights: Screaming cowbirds heavily parasitize greyish baywings in Argentina. Genetic data showed that multiple unrelated cowbirds parasitize the same host. However, repeat parasitism on the same host nest by the same parasite was rare. Avoidance of repeat parasitism is consistent with mental 'bookkeeping' by cowbirds.